1982
DOI: 10.1172/jci110527
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of natural killing in vitro by monocytes and polymorphonuclear leukocytes: requirement for reactive metabolites of oxygen.

Abstract: A B S T R A C T Natural killer cells spontaneously lyse certain tumor cells and may defend against malignancy. We have previously shown that natural killing (NK) by human peripheral blood mononuclear cells (PBMC) is suppressed in vitro by phorbol diester tumor promoters, including 12-0-tetradecanoylphorbol-13-acetate (TPA). We here demonstrate that suppression of NK is mediated by monocytes or polymorphonuclear leukocytes (PMN) and that suppression is dependent on the generation of reactive forms of molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
54
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 65 publications
4
54
0
Order By: Relevance
“…Experimental work in the mouse has suggested that oestrogens may influence NK levels (Seaman et al, 1978). Seaman et al (1979b) have shown that mouse oestradiol, which is itself non-toxic for NK cells (Seaman et al, 1978(Seaman et al, , 1979a, may suppress NK activity, perhaps via its effect on the bone marrow, though doses of oestradiol 9 times the physiological level are required for 4-6 weeks before a decline in activity is seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental work in the mouse has suggested that oestrogens may influence NK levels (Seaman et al, 1978). Seaman et al (1979b) have shown that mouse oestradiol, which is itself non-toxic for NK cells (Seaman et al, 1978(Seaman et al, , 1979a, may suppress NK activity, perhaps via its effect on the bone marrow, though doses of oestradiol 9 times the physiological level are required for 4-6 weeks before a decline in activity is seen.…”
Section: Discussionmentioning
confidence: 99%
“…Seaman et al (1979b) have shown that mouse oestradiol, which is itself non-toxic for NK cells (Seaman et al, 1978(Seaman et al, , 1979a, may suppress NK activity, perhaps via its effect on the bone marrow, though doses of oestradiol 9 times the physiological level are required for 4-6 weeks before a decline in activity is seen. Neonatal administration of diethyl stilboestrol also suppresses NK activity (Kalland, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…T helper cells appear to be particularly sensitive to inhibition by DP and copper sulfate (17,18), although a recent study suggests that B lymphocytes are more sensitive to H202 than are T celis (19). Natural killer cell function is also inhibited by reactive oxygen species released from activated monocytes and polyrnorphonuclear leukocytes (20). DP complexed with copper also has superoxide dismutase activity (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of in vitro and in vivo observations from independent laboratories have supported the observation of oxidative suppression of NK and T cells by phagocytes (i.e. monocytes, macrophages and neutrophils) (Seaman et al, 1982;Finke et al, 1993;Tartour et al, 1995;Hansson et al, 1996a;Kono et al, 1996;Saio et al, 2001). Hellstrand and co-workers have demonstrated that histamine protects NK and T cells against oxygen radical-induced dysfunction and apoptosis by specifically blocking the formation and release of hydrogen peroxide (H 2 O 2 ) from phagocytes, and moreover, maintains the activation of NK and T cells by IL-2 (Hellstrand and Hermodsson, 1986, 1991Hellstrand et al, , 1994aAsea et al, 1996;Hansson et al, 1996bHansson et al, , 1999.…”
Section: Toxicitymentioning
confidence: 95%
“…However, the new paradigm of tumours arising and persisting in the setting of chronic inflammation (Pollard, 2004;Vakkila and Lotze, 2004) may represent one of several factors of importance for treatment failure. Among macrophage and neutrophil products, reactive oxygen species (ROS) may not only induce genomic instability (O'Byrne and Dalgleish, 2001) but also damage antitumour immune effector cells, especially natural killer (NK) and T cells (Seaman et al, 1982;Hellstrand et al, 1994a;Hansson et al, 1996a). Intratumoural macrophages isolated from melanoma metastases inhibit NK cell function by the release of ROS (Kono et al, 1996).…”
mentioning
confidence: 99%